2017
DOI: 10.1093/ijnp/pyx045
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Olfactory Integration in Schizophrenia: Functional Connectivity Study

Abstract: BackgroundEvidence for olfactory dysfunction in schizophrenia has been firmly established. However, in the typical understanding of schizophrenia, olfaction is not recognized to contribute to or interact with the illness. Despite the solid presence of olfactory dysfunction in schizophrenia, its relation to the rest of the illness remains largely unclear. Here, we aimed to examine functional connectivity of the olfactory bulb, olfactory tract, and piriform cortices and isolate the network that would account for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…They observed that schizophrenic people appear to have a reduced assortment of pleasant odors compared to healthy subjects and they report smells as less good over the controls [193,196,198], being in line with other reports [66,193,196,198,199]. Functional and structural alterations of the olfactory circuitry have been observed in schizophrenic patients using fMRI analysis [200] and electro olfactogram (EOG) measuring olfactory evoked potentials (EP) [194,201]. At the biomarker level, cell culture preparations from nasal epithelium showed an alteration in G protein-coupled receptors (GPCRs) cascade, likely affecting the olfactory processing observed in this psychiatric disorder [202].…”
Section: Schizophrenia and Autismsupporting
confidence: 79%
“…They observed that schizophrenic people appear to have a reduced assortment of pleasant odors compared to healthy subjects and they report smells as less good over the controls [193,196,198], being in line with other reports [66,193,196,198,199]. Functional and structural alterations of the olfactory circuitry have been observed in schizophrenic patients using fMRI analysis [200] and electro olfactogram (EOG) measuring olfactory evoked potentials (EP) [194,201]. At the biomarker level, cell culture preparations from nasal epithelium showed an alteration in G protein-coupled receptors (GPCRs) cascade, likely affecting the olfactory processing observed in this psychiatric disorder [202].…”
Section: Schizophrenia and Autismsupporting
confidence: 79%
“…Data preprocessing and statistical analyses were conducted using FMRIB Software Library as well as Analysis of Functional NeuroImages (AFNI). The preprocessing stream has been described in our previous study (Kiparizoska & Ikuta, ). Briefly, skull stripping and segmentation were performed on the structural volume, as well as its co‐registration to the EPI volumes.…”
Section: Methodsmentioning
confidence: 99%
“…We used Stroop task fMRI data ( ) [ 20 ], since activation patterns for the Stroop task is relatively well known. Preliminary data processing followed previous publication [ 23 ]. Using FMRIB Software Library (FSL) as well as Analysis of Functional NeuroImages (AFNI), anatomical volume was skull stripped, segmented (gray matter, white matter and CSF), and registered to the MNI 2mm standard brain.…”
Section: Methodsmentioning
confidence: 99%